Buprenorphine implementation at syringe service programs following waiver of the Ryan Haight Act in the United States. (1st August 2022) - Lambdin, Barrot H.; Bluthenthal, Ricky N.; Tookes, Hansel E.; Wenger, Lynn; Morris, Terry; LaKosky, Paul; Kral, Alex H.
Abstract: Introduction: Among people with an opioid use disorder in the United States, only 10% receive buprenorphine treatment. The Ryan Haight Act is a federal law that has regulated buprenorphine delivery, requiring an in-person examination between a patient and provider before initiating treatment. At the beginning of the COVID-19 pandemic, federal agencies waived in-person examination requirements for buprenorphine treatment initiation. We examined whether Ryan Haight Act waiver improved implementation of telehealth buprenorphine within syringe service programs (SSPs) – organizations that serve people with historically low access to treatment. Methods: We surveyed all known SSPs operating in the US in 2021 (N = 421) of which 77% responded (n = 325). We calculated the prevalence and accompanying 95% confidence intervals (CI) for implementation of telehealth buprenorphine inductions at SSPs in 2020. Multivariable logistic regression was used to assess differences in implementing telehealth buprenorphine inductions by organizational characteristics. Results: In 2020, the prevalence of implementing buprenorphine inductions via telehealth was 24% (95% CI:19–30%). Non-governmental SSPs had a higher odds of telehealth buprenorphine inductions (adjusted odds ratio (aOR) = 2.92; 95% CI:1.22–7.00; p = 0.016), compared to governmental SSPs. Furthermore, the larger the organization's annual budget, the higher the odds of telehealth buprenorphine implementation (aOR = 2.00 per quartile (95% CI:1.33–2.99; p = 0.001). SSPs located in states with higher opioid overdose mortality rates did not have significantly higher likelihood of telehealth buprenorphine implementation. Conclusion: A substantial number of SSPs implemented telehealth buprenorphine after waiver of the Ryan Haight Act. Permanent adoption of this waiver will be critical and providing financial resources to SSPs is vital to support implementation of new innovations. Highlights: After waiver of the Ryan Haight Act, 24% of SSPs began offering telehealth buprenorphine to their participants in 2020. Non-governmental syringe service programs were more likely to implement telehealth buprenorphine. Organizations with larger annual budgets were more likely to implement telehealth buprenorphine. Opioid overdose mortality rates were not related to likelihood of telehealth buprenorphine implementation.